Idade de desmame: respostas comportamentais, fisiológicas e zootécnicas de cordeiros mestiços Santa Inês Dorper e ovelhas Santa Inês - Rodrigues, Alice Deléo [UNESP] (2014)
The sheep breeding stands out as an opportunity in Brazilian livestock. For this reason, there is growing demand for information about the species, including information of management strategies to improve the productive system. In this context, 44 Santa Inês ewes and 58 ½ Santa Inês ½ Dorper lambs were evaluated during two consecutive lactations in order to determine the effects of two weaning ages, at 45 or at 60 days of age. In this study, behavioral measurements and blood samples were taken at weaning and also after it to determine the cortisol levels through administration of adrenocorticotropic hormone (ACTH). Cortisol levels, behavior measurements, weight and weight gain were analyzed using proc Mixed of SAS program. Means tests were done with 5% of significance (P<0.05). Cortisol levels at weaning for ewes and lambs were not different for the two weaning ages evaluated. For ewes, the highest cortisol levels were observed 24 h after weaning and the establishment of basal levels occurred 48 h after weaning. For lambs, on the other hand, reductions in cortisol levels were verified 6 and 12 h after weaning and establishment of basal levels one day after. After ACTH administration, cortisol curves aspect for ewes and lambs were very similar, therefore, highest liberation of cortisol was verified for the ewes. Between the five ewes with highest cortisol levels, 57.14% of their lambs had cortisol higher than the other cortisol lambs means. For weaning and ACTH administration, the response profile of ewes was repeated over the two years of evaluation (P<0.0001). For lambs, also no differences were found for weight and weight gain in the two ages of weaning, at 45 and at 60 days (P=0.11). Positive correlations between weight and high cortisol levels and between weight gain and lower cortisol levels were also verified. Lamb´s behaviors “Feeding, Inactivity and Standing in the shadow were influenced by weaning age and the ...